NOVEL THERAPEUTIC APPLICATIO OF MICROBUBBLES FOR TARGETED DRUG DELIVERY - SUBHABROTA MAJUMDAR; SUBHADEEP CHOWDHURY (International Journal of Pharma and Bio Sciences, 2010)
Blood-brain barrier impermeability presents a problem while treating malignant and degenerative disorders of the central nervous system, such as brain cancer, Alzheimer’s and Parkinson’s disease. The protective blood-brain barrier blocks many drugs from acting on brain cells. A method for delivering drugs directly to the affected area may increase the effectiveness of chemotherapy in brain tumors and reduce its toxic effect on healthy cells. The new innovative technique that uses ultrasound and drug-laden “microbubbles” to deliver concentrated chemotherapy drugs to the inner lining of blood vessels. Microbubbles destruction has been proposed as an innovative method for noninvasive delivering of drugs and genes to different tissues. They are used to carry a drug until a specific area of interest is reached, and then ultrasound is used to burst the microbubbles, causing site-specific delivery of the bioactive materials. The microbubbles as drug carriers have an average size less than that of red blood cells, i.e. they are capable of penetrating even into the small blood capillaries and releasing drug and genes under the action of ultrasound field. Targeting ligands are attached to the surface of the microbubbles (i.e. targeted-microbubbles), which have been widely used in cardiovascular system and tumor diagnosis. This review focuses on the characteristics of microbubbles that give them therapeutic properties and some important aspects of ultrasound parameters that are known to influence microbubblemediated drug delivery. In addition, current studies involving this novel therapeutic application of microbubbles will be discussed.